Пути повышения радиорезистентности персонала объектов атомной энергетики - Ивницкий, Ю.Ю.; Гребенюк, А.Н.; Рейнюк, В.Л.; Легеза, В.И. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2005)
Разработана концепция применения медицинских средств противорадиационной защиты персонала объектов атомной энергетики, включающая порядок применения профилактических противорадиационных средств для случаев облучения не только в благоприятных, но и при неблагоприятных температурных условиях. Отражены принципы формирования системы медицинских средств повышения радиорезистентности персонала объектов атомной энергетики. Розроблено концепцію застосування медичних засобів протирадіаційного захисту персоналу об’єктів атомної енергетики, що містить у собі порядок застосування профілактичних протирадіаційних засобів на випадок опромінення не тільки за сприятливих, але й за несприятливих температурних умов. Наведено принципи формування системи медичних засобів підвищення радіорезистентності персоналу об’єктів атомної енергетики. The flexible system of medical anti-radiation remedies proposed for the protection of the stuff of atomic electrical stations and of troops participating in emergency works. The system suggests the possibility of option of accessible anti-radiation remedies. Hence, medical stuff must be acquainted with not only pharmaceuticals producing in the country, but also reserve remedies, including food supplements. Discussed are the principles of relevant choice of remedies belonging to following groups: radio protectors, inductors of prolonged state of elevated radio-resistance, and remedies preventing the early neurological manifestations of cerebral radiation syndrome.